Mental Predicate Feel Subtype Feel and Think in Japanese: A Natural Semantic Metalanguage Approach (e-Journal of Linguistics, 2019)
According to Goddard and Wierzbicka (2014) the original meaning of the mentalpredicate consists of six types namely, think, know, feel, see, hear, want and don't want. Thisfinding was then forwarded to Japanese by Asano Cavanagh (2015), finding 12 verbs ofJapanese language conditions that are matched with those found by Goddard and Wierzbicka(2014). Of the twelve state verbs that were passed on by Asano, the type FEEL was matchedwith the mental predicate 感じるkanjiru. Mental predicate感じるkanjiru has a subtype whichturns out to produce more mental predicate than the other six types. Found subtypes FEEL andTHINK, FEEL and HAPPEN, FEEL and DO, FEEL and TELL. Subtype FEEL and THINKproduces 2 sub-subtypes namely FEEL and THINK (GOOD) and FEEL and THINK (BAD).
Keywords: mental predicate; feel; type; subtype